2020
DOI: 10.32859/era.20.57.1-36
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative study on medicinal plants traded in selected herbal markets of Khyber Pakhtunkhwa, Pakistan

Abstract: Background: This study is the first large-scale medicinal plant survey in the herbal markets of seven Districts of Khyber Pakhtunkhwa, Pakistan. The study provides the first significant catalogue on medicinal plants trade, price patterns, routes and utilization.Methods: Based on semi structured questionnaires, interviews and group discussions with 210 informants (92.86% men and 7.14% women) and personal observations were conducted.Results: A total of 161 plant species and three species of fungi were documented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Artemisia absinthium is used against malaria, diabetes, as tonic, for blood pressure. It is also known as blood purifier (Khan & Khatoon 2008;Ashrif et al 2010;Murad et al 2012;Abbas et al 2018;Hussain et al 2018a;Muhammad et al 2019;Abbas et al 2020;Shah et al 2020). In our study it was used for the treatment of digestive problem, jaundice as well as Covid-19.…”
Section: Relevance Of the Studymentioning
confidence: 67%
See 1 more Smart Citation
“…Artemisia absinthium is used against malaria, diabetes, as tonic, for blood pressure. It is also known as blood purifier (Khan & Khatoon 2008;Ashrif et al 2010;Murad et al 2012;Abbas et al 2018;Hussain et al 2018a;Muhammad et al 2019;Abbas et al 2020;Shah et al 2020). In our study it was used for the treatment of digestive problem, jaundice as well as Covid-19.…”
Section: Relevance Of the Studymentioning
confidence: 67%
“…There is however not a single specimen reported from Central Kurram. Floristically and ethnobotanically this area has not been explored by researchers Hussain et al 2013;Hussain et al 2018a;Shah et al 2020;Hussain et al 2021). In the ethnobotanical literature of Pakistan, some research has been published on the Ethnomedicinal use of plants on Upper and Lower Kurram such as Ajaib et al 2014, reported 45 species from Agra Valley Parachinar, Kurram. They documented that one-third species has single-usage, two and multiple usage shrubs were consumed for crafting (25%), medicinal (22.5%), culinary (11%) miscellaneous and other purposes.…”
Section: Introductionmentioning
confidence: 99%
“…This changing climate increases the intensity and frequency of the abiotic factors that contrarily reduced agricultural production [ 13 ]. In these abiotic factors, temperature is the key factor affecting seed germination parameters in all plants [ 14 ]. However, it is significant that each taxon requires a certain range of T s for seed germination called cardinal temperatures [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Seed Vigor Index = Seedlings length(cm) × Seed Germination %age (17) 2.5.10. Seed Vigor Index-II (SVI-II)…”
Section: Mean Germination Rate (Mgr)mentioning
confidence: 99%
“…It is a complex physiological process that is affected by environmental stress factors, including temperature (T), water availability, salinity, light, and chemical materials [10][11][12][13][14][15][16]. It has been indicated, however, that temperature and water availability are the main factors influencing SG by affecting seed dormancy, enzymatic activity, hormonal biosynthesis, and translocation of reserve store materials [7,8,17,18]. Furthermore, the ability of the seed to absorb water also determines the success or failure of SG; however, this is determined by soil moisture levels [12].…”
Section: Introductionmentioning
confidence: 99%